Autonomous patrol and surveillance system using unmanned aerial vehicles - Lee, K.S. (Institute of Electrical and Electronics Engineers Inc., 2015)
Unmanned aerial vehicles (UAVs) are increasingly popular for civil applications due to their flight capabilities and mobility. This paper proposes an indoor autonomous patrol and surveillance system using unmanned aerial vehicles. The system consists of six components: (1) a low cost vision-based pose estimation of UAVs, (2) vision-based state estimation, (3) UAV patrol path planning, (4) UAV controller to desired waypoints, (5) manual joystick controller and (6) assignment of priority hierarchy to multiple control inputs of a robot. The components were integrated successfully and the designed system was experimented in an indoor setup. Results has shown that the proposed system is suitable and feasible to be used as an autonomous patrol and surveillance agent for indoors use. Â© 2015 IEEE.